Assurance in vaccine efficacy clinical trial design based on immunological responses. Issue 7 (12th July 2021) - Callegaro, Andrea; Zahaf, Toufik; Tibaldi, Fabian
Abstract: The assurance of a future clinical trial is a key quantitative tool for decision‐making in drug development. It is derived from prior knowledge (Bayesian approach) about the clinical endpoint of interest, typically from previous clinical trials. In this paper, we examine assurance in the specific context of vaccine development, where early development (Phase 2) is often based on immunological endpoints (e.g., antibody levels), while the confirmatory trial (Phase 3) is based on the clinical endpoint (very large sample sizes and long follow‐up). Our proposal is to use the Phase 2 vaccine efficacy predicted by the immunological endpoint (using a model estimated from epidemiological studies) as prior information for the calculation of the assurance.